The Clinical Eye: A Need to Improve the Teaching of Semiology in Undergraduate Medical Education - Carlos Jesús Toro-Huamanchumo; Carlos Jesús Toro-Huamanchumo; Laura Rosa Arce-Villalobos; Laura Rosa Arce-Villalobos (International Journal of Medical Students, 2014)
NA